The Returns to Schooling: A Selectivity Bias Approach with a Continuous Choice Variable - Garen, John (Econometrica, 1984)
The essence of selection bias is that we do not observe nonoptimal choices. This applies whether the choice variable is discrete or continuous. This paper extends the selection bias methodology to the case where the choice variable is continuous and the choice set is ordered. The leading practical application of this analysis is the schooling choice problem. Schooling is treated as a continuous choice variable and selectivity corrected rates of return are estimated. The findings suggest selectivity is of considerable importance and support the comparative advantage hypothesis of Willis and Rosen [18].